IDENTIFIKASI MISKONSEPSI PESERTA DIDIK PADA MATERI GERAK PARABOLA DI SMA TARUNA BUMI KHATULISTIWA - Tarik Tamara; Stepanus Sahala S; Syaiful B Arsyid (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe and find the causes of misconceptions among students at SMA TarunaBumi Khatulistiwa about parabolic motion. This misconception causes the learning objectives ofstudents at SMA Taruna Bumi Khatulistiwa not to be achieved. Based on the interview, there were3 causes of misconceptions experienced by students at Taruna Bumi Khatuliwa Senior HighSchool that were expressed directly by the teaching teacher, including: 1.Lack of students'numeracy skills in solving equations, 2. Students experiencing misconceptions in analyzingphenomenon of parabolic motion, 3. Lack of student interest in learning physics, especiallyparabolic motion. It is for this reason that the authors want to identify the causes and types ofmisconceptions experienced by students at SMA Taruna Bumi Khatulistiwa. The method used isa simple descriptive method with a sample of the entire population of class XI MIPA, as many as55 people. Data collection uses diagnostic tests with open reasons and interviews. The results ofthe analysis showed that students' misconceptions reached 41.57% about the motion of theparabola and the rest did not answer the questions given. Based on the results of interviews withstudents, the causes of misconceptions originating from the students themselves on parabolicmotion material include: students' initial conception, incomplete reasons and student abilities.These findings are expected to be used as material for consideration in choosing the appropriatetreatment to overcome students' misconceptions.Keywords: Identification, Misconception, Projectile motion